Child Empowerment and Safeguarding in the UAE: The Role of Picturebooks for Emirati Children - Sarah L. Nesti Willard; Fawzia Gilani-Williams (CLELEjournal)
This paper presents a reflective ethnography documenting the creation and use of picturebooks in the United Arab Emirates (UAE), aimed at supporting the safeguarding of children within English Language Teaching contexts for primary and lower secondary students.